Summer Internship - Mehta, Hirali Piyush (ATLAS SkillTech University, 2024)
The agency's emphasis on collaboration and a customer-centric approach taught me the importance of understanding the clients' needs and tailoring solutions to meet their specific objectives. I also learned how to use data-driven insights to optimize marketing strategies and achieve measurable results.
Project Report on Summer Internship (2022-24) Under the Guidance of Prof. Hirali Piyush Mehta
Keywords: customer-centric; tailoring solutions; data-driven insights